Correlation of tumor size and immunohistochemistry status with lung metastasis in carcinoma breast - Gayathre, S. P.; Maniselvi, S. (International Surgery Journal, 2018)
Background: Breast cancer is common cancer among females in rural India and is rapidly catching up to cervical cancer in rural India. Metastasis can occur after the initiation of treatment or at the time of diagnosis. The stage at initial presentation and underlying biology of the tumor has an impact on prognosis and metastasis of the tumor. The objective of the study was to study the correlation between tumor size and lung metastasis and to find the correlation between ER, PR status, and lung metastasis. Methods: This study was conducted in 82 patients with breast carcinoma coming to the department of the general surgery and oncology at Government Stanley Medical College and Hospital. Details of cases and full history obtained. Routine blood investigations were done. Tumor size is evaluated by clinical examination and imaging. For all patients, core needle biopsy is done to confirm the diagnosis and receptor status. IHC status of the tumor is obtained from the pathologist. Presence of lung metastasis documented by CECT chest. Results: In this study, the prevalence rate of lung metastasis in carcinoma breast patients is 9.75% Total number of Carcinoma Breast are 82, in which lung metastasis is seen in 8 cases and CECT chest is normal in 74 patients. The prevalence rate of lung metastasis in ER-positive patients is 9.90%. The prevalence rate of lung metastasis in ER-negative patients is 10.81%. The prevalence rate of metastasis in PR positive patients is 9.52%. The prevalence rate of metastasis in PR negative patients is 10%. Of 34 cases with HER-2 positive status 3 patients presented with lung metastasis with a prevalence rate of 8.82%. Of 48 cases with HER-2 negative status 5 cases presented with lung metastasis with a prevalence rate of 10.42%. Conclusions: In this study prevalence of lung metastasis in carcinoma breast is 9.75%. There seems to be no correlation between ER, PR and HER-2 neu status and lung metastasis. There is also no correlation between clinically T2 and T3 tumors and lung metastasis. Whereas clinically T4 tumors seem to have a higher incidence of lung metastasis.